Anisotropic interpolation method of silicon carbide oxidation growth rates for three-dimensional simulation. (February 2017) - Šimonka, Vito; Nawratil, Georg; Hössinger, Andreas; Weinbub, Josef; Selberherr, Siegfried
Abstract: We investigate anisotropical and geometrical aspects of hexagonal structures of Silicon Carbide and propose a direction dependent interpolation method for oxidation growth rates. We compute three-dimensional oxidation rates and perform one-, two-, and three-dimensional simulations for 4H- and 6H-Silicon Carbide thermal oxidation. The rates of oxidation are computed according to the four known growth rate values for the Si- ( 0 0 0 1 ), a- ( 1 1 2 ¯ 0 ), m- ( 1 1 ¯ 0 0 ), and C-face ( 0 0 0 1 ¯ ) . The simulations are based on the proposed interpolation method together with available thermal oxidation models. We additionally analyze the temperature dependence of Silicon Carbide oxidation rates for different crystal faces using Arrhenius plots. The proposed interpolation method is an essential step towards highly accurate three-dimensional oxide growth simulations which help to better understand the anisotropic nature and oxidation mechanism of Silicon Carbide.